Irene de Matías - CO2 Rich Streams Methanization Intensified by Steam Adsorption with LTA Zeolites in Fluidized Bed Reactor - de Matías, Irene (Jornada de Jóvenes Investigadores del I3A, 2022)
CO2 Rich Streams Methanization Intensified by Steam Adsorption with LTA Zeolites in Fluidized Bed Reactor